2019
DOI: 10.29252/jommid.7.4.116
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Quantitative Real-Time Polymerase Chain Reaction (qRT-PCR) and Agglutination Assays in Diagnosis of Brucellosis in Golestan Province, North of Iran

Abstract: Introduction: Brucellosis is one of the most common zoonotic infections worldwide. The clinical symptoms of brucellosis are similar to a wide range of diseases; hence, reliable diagnostic and laboratory methods are required to identify the causative agent. Iran is an endemic region of brucellosis, and many patients are misdiagnosed due to the nature of the infection. In this study, we aimed to evaluate and compare the use of the conventional Wright test and quantitative polymerase chain reaction (qPCR) for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…Differences in the sensitivity and specificity of PCR samples in studies can be due to differences in PCR kits, the disease stage, and the method of DNA extraction from serum or whole blood samples of patients. False negatives in the PCR sample can be attributed to technical errors, the inefficiency of the chemicals used, low DNA content in the serum sample, and previous use of antibiotics (17,(28)(29)(30). The current study showed that the PCR method has high accuracy, specificity, and sensitivity, promoting the importance of using this method as a reliable early diagnostic test in human brucellosis, especially in suspected patients with seronegative tests.…”
Section: Discussionmentioning
confidence: 63%
“…Differences in the sensitivity and specificity of PCR samples in studies can be due to differences in PCR kits, the disease stage, and the method of DNA extraction from serum or whole blood samples of patients. False negatives in the PCR sample can be attributed to technical errors, the inefficiency of the chemicals used, low DNA content in the serum sample, and previous use of antibiotics (17,(28)(29)(30). The current study showed that the PCR method has high accuracy, specificity, and sensitivity, promoting the importance of using this method as a reliable early diagnostic test in human brucellosis, especially in suspected patients with seronegative tests.…”
Section: Discussionmentioning
confidence: 63%